EVALUASI PROGRAM PELATIHAN KOGYO SENMON (KOSEN) DI PERSEROAN TERBATAS DN - Huda Nur Rohmat, Huda Nur Rohmat; Abdul Rahman A. Ghani; Elin Driana; Sugiarto (Jurnal Penelitian dan Penilaian Pendidikan, 2024)
This evaluation aims to assess the effectiveness of the KOGYO SENMON(KOSEN) training conducted by Perseroan Terbatas (PT) DN. The training evaluationused the Kirkpatrick evaluation approach consisting of four aspects includingparticipant reactions, material mastery, behavior change, and results achieved. Datawere obtained through evaluation results, document studies, and questionnaires. Dataprocessing was carried out using quantitative descriptive methods. The results of theevaluation of participants' reaction to the organizers were included in the "Satisfied"qualification with an average score of 87. After the evaluation, it was found that theaverage score of participants in learning was 88, so they managed to meet thequalification of "Good". The behavior measurement based on the assessment fromsuperiors and colleagues received an average score of 85 with the criteria of "Good".While the evaluation of the result stage after the participants have completed thetraining with an average score of 83, qualifying as "Good". The evaluation of PT DN'sKOSEN training using Kirkpatrick can identify and evaluate all elements of trainingand is worthy of being used as a reference.